Violation of orthographic norms in the daily newspaper "Bota Sot" - Duraj, Petrit; Dulaj, Fridrik (Technium Social Sciences Journal, 2023)
This study aims atexpressing the difficulties that the media have in the spelling of the Albanian language. More precisely, the written media, that is, the newspapers that are published in physical form and those that are only found in the online version. The unified orthography of a language, in our case of the Albanian language, is a term of the crystallization of the national literary norm in all the main chains of the phonetic, word formation,grammatical, and lexical structure. It reflects the current state and general trends of the development of our literary language. Today's orthography aims for further unification of the national literary language norm on the basis of the common forms that have been adopted and are being adopted by it. Given that the basic principle of Albanian orthography is the phonetic principle followed by the grammatical one, and seeing the constant spelling errors of the speakers and those who write in the Albanian language, weexamined a daily newspaper, which has many readers and has a huge impact on Albanian speakers.In order to see the most frequent spelling errors, we will outline and analyze the wrong cases and give the correct forms based on the Albanian standard. Thus, from the results that will be brought, we will see the greatest difficulties faced by journalists of this daily newspaper, as well as their challenges on using the correct forms.